Incorporating e-learning into a Local Government Authority Context: Evaluating Developers’ Perspectives on the Learning Ladder Project - Smith, Christine; Zenios, Maria (Proceedings of the International Conference on Networked Learning, 2006)
In this paper, we describe the evaluation of an e-learning project. The Learning Ladder developed a number of e-learning modules for local government staff on recurrent working practices. The modules feature the use of short video clips as a means to support and encourage organisational learning . We report on one part of the evaluation: namely, the qualitative analysis of data from developers. We focus on three aspects: developers’ perceptions of video clips for learners to reflect upon examples of working practices; their perceptions on the role of e-learning for a consistent approach to organisational learning; and perceptions on developing a learning community. Findings suggest there is value in video for capturing authentic practices and for creating consistency in representations of organisational policy and practice. However our findings suggest the organisation has only made limited progress towards creating a learning culture.